(untitled) (Confluenţe Bibliologice, 2013)
On 5-6 September, 2013, in Făgăraş took place the ﬁrst session of scientiﬁc communications, which refers to exploitation of country’s speciﬁc cultural heritage of Făgăraş. The session was held in the Medieval Tower Thomory from the Museum of History.